TREATMENT OF ORTHODONTICALLY INDUCED GINGIVAL HYPERPLASIA BY DIODE LASER - CASE REPORT - Prabhu, Manavi; Ramesh, Amitha; Thomas, Biju (Journal of Health and Allied Sciences NU, 2015)
It is well known that excessive gingival display in the anterior region can have a very negative impact on the patients smile and psychology. This excessive gingival display could be due to gingival enlargement or altered passive eruption of the teeth. These defects can be corrected through periodontal surgeries. This case report describes successful aesthetic crown lengthening in maxillary and mandibular anterior teeth using diode laser.
Keywords: anterior crown lengthening; diode laser; gingivectomy; gingivoplasty